Megafans of the Pantanal Basin, Brazil - Santos, Mauricio G. M.; Stevaux, Jose C.; Assine, Mario L. [UNESP]; Wilkinson, M. J.; Gunnell, Y. (Cambridge Univ Press, 2023)
The Pantanal Basin (west-central Brazil) is one of the largest alluvial wetlands in the world (> 150,000 km(2)) formed dominantly by coalescing Quaternary megafans. The Pantanal Basin is an efficient sediment trap: of 25Mt yr(-1) of suspended load that enters by the main river systems, only 10Mt yr(-1) is exported by the trunk river. Sediments are sourced by multiple rivers draining Precambrian lowlands and Paleozoic uplands. The eastern border displays tablelands of Paleozoic rocks of the Parana Sedimentary Basin, with lowlands of Precambrian rocks on the northern, southern and western borders. The Taquari, Cuiaba, and Sao Lourenco megafans, tributaries to the Paraguay trunk-river system, are the largest fluvial fans in the Pantanal. The Paraguay River itself has produced two relatively small megafans. The megafans display four main landform assemblages: incised meander belts proximally, active aggradational lobes, abandoned degradational lobes, and mixed-process floodplains. Megafan surfaces display palaeodrainage networks ranging from braided channel planforms to the current meandering and anabranching planforms. Megafan areas seem to be a function of both feeder-basin area and catchment geology: those fed from sedimentary rock outcrops are larger, with more complex barform development than those supplied from Precambrian basement catchments.